Effectiveness Methods In Determining The Cost of Ffb Production In Palm Oil Plantations - Renny Masyarah (Jurnal Mantik, 2022)
This study explains the factors that can affect the determination of the cost of producing fresh fruit. When the Company determines production costs, the Company PT. Kartika Hijau Lestari performs calculations using the complete cost method. Where the total cost method is the determination of production costs in determining the correct price of production, a company must consider the components of production costs consisting of direct material costs, direct labor costs, and overhead costs. All these costs are costs associated with the production process. The results showed that the total cost of production in December 2021 was 62,257,798 rubles and produced 9,972 kg of fresh fruit. The cost of producing fresh fruit was 1,027 rubles/kg. Based on the results of the study, it can be stated that the direct material costs of PT. Kartika Hijau Lestari owns fresh fruit bunches purchased from the Company's plantations, and in determining the selling price of fresh fruit bunches, PT. Kartika Hijau Lestari monitors market prices.